An Experimental Investigation of the Structural Properties of High Modulus Aluminium Alloy - Howe, D.; Soper, N. C. (College of Aeronautics, 1956)
The purpose of this report is to give the results of an experimental investigation of the structural properties of high modulus aluminium alloy. The tests carried out consisted of tension, compression, hardness, bending and compression panel investigations. It was found that high modulus material is difficult to form and very prone to cracking on failure. Thus although the material has a definite structural application, in view of the forming and cracking problems it is doubtful whether further development is worthwhile.